Thrombotic events and COVID-19 vaccines - Brazete, C. (2021)
COVID-19 vaccines are considered promising agents in the control of the pandemic. Although their safety was assessed in randomised clinical trials, severe adverse events (AEs) have been reported after large-scale administration. This study aims to evaluate thromboembolic AEs reported after vaccination in a real-world context and how they led to the interruption of vaccination campaigns. We also review the benefits and risks of the vaccines approved in the European Union and provide recommendations. A review of the literature was performed using Medline/PubMed electronic database as well as institutional and pharmacovigilance official reports. Our findings show that vaccine-induced prothrombotic immune thrombocytopenia has been suggested as a very rare AE associated with viral vector vaccines. Unusual thrombotic events combined with moderate-to-severe thrombocytopenia were reported mainly in women under 60 years of age. As safety signals emerged, Vaxzevria and Janssen´s COVID-19 vaccine campaigns have been paused while investigations proceed. On the other hand, the number of deep vein thrombosis and pulmonary embolism reports have not increased. Post-marketing surveillance indicated that mRNA vaccines are safe and should continue to be used. The thrombotic events report rate is not increased in people over 60 years. As they are at greater risk for COVID-19 complications and death, no vaccine restrictions are recommended in this group. Risk factors for vaccine-induced prothrombotic immune thrombocytopenia should be established so that evidence-based decisions can be made. Systematic monitoring of COVID-19 vaccine safety is essential to ensure that the benefits of vaccination outweigh the risks.